ONLINE AUTHENTIC MATERIALS IN TEACHING ENGLISH FOR EFL STUDENTS - Pujainda Mandarsari (International Journal of Research on English Teaching and Applied Linguistics, 2023)
This qualitative case study investigates the use of online authentic materials in teaching English at SMPN 2 Tinambung . The study aims to identify the types of online authentic materials used, teachers’ perceptions of their use, and the challenges faced by teachers in using them. Two English teachers were selected using purposive sampling. The results show that teachers used various types of online authentic materials such as YouTube videos, Google pictures, online articles, online news, podcasts, and web short stories. The teachers perceived online authentic materials to be similar to face-to-face authentic materials, but with different media. They were able to adapt the materials based on their needs and purposes. However, they preferred face-to-face meetings due to fewer problems. Challenges in the implementation of online authentic materials included internet connection, classroom management, and language difficulty.